2014
DOI: 10.1155/2014/260287
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Fredholm Solvability in the Framework of Singular Solutions for the (3+1)-D Protter-Morawetz Problem

Abstract: For the four-dimensional nonhomogeneous wave equation boundary value problems that are multidimensional analogues of Darboux problems in the plane are studied. It is known that for smooth right-hand side functions the unique generalized solution may have a strong power-type singularity at only one point. This singularity is isolated at the vertex of the boundary light characteristic cone and does not propagate along the bicharacteristics. The present paper describes asymptotic expansions of the generalized sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Even in the linear case, the question of well-posedness is surprisingly subtle and not completely resolved (see [32] , [1] and [2] [32] it was shown that the homogeneous adjoint problem admits infinitely many nontrivial classical solutions v n ∈ C n (Ω − ), n ∈ N. [31,30].…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the linear case, the question of well-posedness is surprisingly subtle and not completely resolved (see [32] , [1] and [2] [32] it was shown that the homogeneous adjoint problem admits infinitely many nontrivial classical solutions v n ∈ C n (Ω − ), n ∈ N. [31,30].…”
Section: Remarkmentioning
confidence: 99%
“…Actually, if in the definition of the generalized solution (see (31) [31,30]. Currently, we have constructed a singular solution for the same linear Protter problem for wave equation (m=0) with exponential growth of singularity at the point O(see [13] [28], [29].…”
Section: Remark 10mentioning
confidence: 99%
“…This differs the conventional case of propagation of singularities, like in Hörmander [10, Chapter 24.5], since the point O here lies both on the characteristic part of the boundary Σ 2 and on the non-characteristic part Σ 0 . In the special case when the right-hand side function f is a harmonic polynomial, the exact behavior of the generalized solution of Problem P2 is found in [24]. Garabedian [7] proved the uniqueness of a classical solution for a four-dimensional Proter problem.…”
Section: Consider the Wave Equation Inmentioning
confidence: 99%
“…On the other hand, in the more general case, when f ∈ C 6 (Ω) the necessary and sufficient conditions for existence of bounded solutions are given in [24,Theorem 1.3]. These are an infinite number of orthogonality conditions for f .…”
Section: Existence Of a Generalized Solutionmentioning
confidence: 99%
See 1 more Smart Citation